Pier Franco Beatrice, The Philosophy of the Few against the Christians: An Inquiry into the Textual Transmission of Porphyry’s Philosophy according to the Chaldean Oracles, Studies in Platonism, Neoplatonism, and the Platonic Tradition 31, Brill, Leiden 2024, ss. 581 - Osek, Ewa (Vox Patrum, 2025)
Review of the book: Pier Franco Beatrice, The Philosophy of the Few against the Christians: An Inquiry into the Textual Transmission of Porphyry’s Philosophy according to the Chaldean Oracles, Studies in Platonism, Neoplatonism, and the Platonic Tradition 31, Brill, Leiden 2024.